Mobile Payment for “PO Tentrem” Bus Rates Based on E-Wallet - Fanizha Anggraini; Rieke Adriati Wijayanti; Mochammad Taufik (Politeknik Negeri Malang, 2022)
According to the results of a 2022 survey conducted by the Association of Indonesian Internet Service Providers (APJII), internet users in Indonesia continued to increase from 175 million to 220 million users of the total population of Indonesia. The increase was driven by the need for communication during the Covid-19 pandemic in the last two years. Most internet users are on the island of Java, followed by the islands of Sumatra, Kalimantan, Sulawesi, Bali-Nusa, and Maluku-Papua. PT. Tentrem Sejahtera is one of the Inter-City In-Province bus companies based on the island of Java, precisely in East Java. The ordering and payment process is still done manually or offline. Consumers who want to buy tickets must come directly to the terminal, to an authorized agent who has been appointed or do it directly when boarding the bus and make transactions in cash. Where when making manual or cash payments sometimes you have to wait a few minutes to issue money and wait for the ticket given by the conductor, while the level of security in payments is very less, so it is less efficient in this sophisticated era. In addition, there are still unscrupulous brokers at several bus departures who sell tickets that do not match the specified price. This study used the e-wallet electronic payment model method, with a mobile payment system for QRIS-based bus fares. With the National Mercant ID (NMID) listed on the QRIS display, a receipt will be issued on the Thermal Print for proof of payment.